The Implementation Of ESA (Engage, Study, Active) Method To Improve The Students Speaking Ability At The Eight Grade Of SMP N 4 Pematangsiantar - Tiodora Silalahi; Dechy Nafthalia Limbong (Program Studi Pendidikan Bahasa Inggris FKIP, 2023)
The aim of this research was to find out whether the implementation of Engage, Study, Active (ESA) method effective to improve the students speaking ability at the eighth of SMP Negeri 4 Pematangsaintar academic year of 2022/2023. This research used quantitative approach with true-experimental design. The data were obtained by using pre-test and post-test. The data of pre-test and post-test of both groups were analyzed by using descriptive and inferential statistics (SPSS 21). The result of the research shows that the hypothesis testing tcount = 2.777 > ttable = 1.697 at the significant level α = 0.05 with degrees of freedom (df) = 60, it means that Ho is rejected and Ha is accepted. So, the implementation of ESA (Engage, Study, Active) Method affects significantly on students speaking ability at the eight grade of SMP N 4 Pematangsiantar academic year of 2022/2023